Australia : Financial System Stability Assessment. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2019)
This paper presents Financial System Stability Assessment of Australian financial systems. The report highlights that financial supervision and systemic risk oversight have been enhanced. And the authorities have taken successful policy action to calm rapid growth in riskier segments of the mortgage market. Restrictions on the growth of investor loans and the share of interest-only mortgages, as well as the introduction of stronger lending standards, appear to have led to a slowdown in mortgage credit growth, and the housing market is now cooling. Financial supervision shows generally high conformity to international best practices, although there are opportunities to close identified gaps and strengthen arrangements. Steps are recommended to bolster the independence and resourcing of the regulatory agencies, by removing constraints on their policy making powers and providing additional budgetary autonomy and flexibility. The paper explains that greater formalization and transparency of the work of the Council of Financial Regulators would further buttress the financial stability framework.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet